The Role of Antimicrobial Peptides in Influenza Virus Infection and Their Potential as Antiviral and Immunomodulatory Therapy - I-Ni Hsieh; Kevan L. Hartshorn (MDPI AG, 2016)
Influenza A virus (IAV) remains a major threat that can cause severe morbidity and mortality due to rapid genomic variation. Resistance of IAVs to current anti-IAV drugs has been emerging, and antimicrobial peptides (AMPs) have been considered to be potential candidates for novel treatment against IAV infection. AMPs are endogenous proteins playing important roles in host defense through direct antimicrobial and antiviral activities and through immunomodulatory effects. In this review, we will discuss the anti-IAV and immunomodulatory effects of classical AMPs (defensins and cathelicidins), and proteins more recently discovered to have AMP-like activity (histones and Alzheimer's associated β-amyloid). We will discuss the interactions between AMPs and other host defense proteins. Major emphasis will be placed on novel synthetic AMPs derived from modification of natural proteins, and on potential methods of increasing expression of endogenous AMPs, since these approaches may lead to novel antiviral therapeutics.